Neuropathic Allodynia Involves Spinal Neurexin-1β-dependent Neuroligin-1/Postsynaptic Density-95/NR2B Cascade in Rats. (October 2015) - Lin, Tzer-Bin; Lai, Cheng-Yuan; Hsieh, Ming-Chun; Jiang, Jian-Lin; Cheng, Jen-Kun; Chau, Yat-Pang; Ruan, Ting; Chen, Gin-Den; Peng, Hsien-Yu
Abstract : Background: Neuroligin-1 (NL1) forms a complex with the presynaptic neurexin-1β (Nrx1b), regulating clustering of N -methyl-D-aspartate receptors with postsynaptic density-95 (PSD-95) to underlie learning-/memory-associated plasticity. Pain-related spinal neuroplasticity shares several common features with learning-/memory-associated plasticity. The authors thereby investigated the potential involvement of NL1-related mechanism in spinal nerve ligation (SNL)–associated allodynia. Methods: In 626 adult male Sprague–Dawley rats, the withdrawal threshold and NL1, PSD-95, phosphorylated NR2B (pNR2B) expressions, interactions, and locations in dorsal horn (L4 to L5) were compared between the sham operation and SNL groups. A recombinant Nrx1b Fc chimera (Nrx1b Fc, 10 μg, 10 μl, i.t., bolus), antisense small-interfering RNA targeting to NL1 (10 μg, 10 μl, i.t., daily for 4 days), or NR2B antagonist (Ro 25-6981; 1 μM, 10 μl, i.t., bolus) were administered to SNL animals to elucidate possible cascades involved. Results: SNL-induced allodynia failed to affect NL1 or PSD-95 expression. However, pNR2B expression (mean ± SD from 13.1 ± 2.87 to 23.1 ± 2.52, n = 6) and coexpression of NL1–PSD-95, pNR2B–PSD-95, and NL1-total NR2B were enhanced by SNL (from 10.7 ± 2.27 to 22.2 ± 3.94, 11.5 ± 2.15 to 23.8 ± 3.32, and 8.9 ± 1.83 to 14.9 ± 2.27 at day 7, n = 6). Furthermore, neuron-localized pNR2B PSD-95–pNR2B double-labeled and NL1/PSD-95/pNR2B triple-labeled immunofluorescence in the ipsilateral dorsal horn was all prevented by Nrx1b Fc and NL1-targeted small-interfering RNA designed to block and prevent NL1 expression. Without affecting NL1–PSD-95 coupling, Ro 25-6981 decreased the SNL-induced PSD-95–pNR2B coprecipitation (from 18.7 ± 1.80 to 14.7 ± 2.36 at day 7, n = 6). Conclusion: SNL-induced allodynia, which is mediated by the spinal NL1/PSD-95/pNR2B cascade, can be prevented by blockade of transsynaptic Nrx1b–NL1 interactions. Abstract : It was shown that the association of N -methyl-d-aspartate receptor NR2B subunits and postsynaptic density-95 scaffolding protein was enhanced in spinal cord dorsal horn neurons after nerve ligation in rats. The disruption of neurexin-1β–neuroligin-1 interaction reduced allodynia and NR2B–postsynaptic density-95 interactions in nerveligated rats.